Harnessing Nutritional Benefits of Spirulina platensis: Standardization of Cultivating Conditions of Spirulina in Kilimanjaro - Nyakundi, David O.; Cleophas, Phocus (Tanzania Journal of Science, 2021)
Malnutrition remains a challenge in Tanzania, notwithstanding government initiatives and health education geared towards assuaging the problem. According to the World Health Organization (WHO), there will be more than 600,000 severely malnourished children in Tanzania by the year 2030. In particular, protein based malnutrition remains the greatest challenge due to the irreplaceable nature of its essential amino acids. Macronutrients and micronutrients which are found in Spirulina platensis have been recommended by WHO to address malnutrition in developing countries. Spirulina platensis is a ﬁlamentous Cyanobacterium microalgae with the highest recorded protein content of plant origin with several immune boosting nutrients. Spirulina cultivation requires sufficient aeration, proper light intensity and salinity for maximum biomass yield, cell productivity, specific growth rate, and protein content. This paper presents the findings of a study carried out in Kilimanjaro on the optimized conditions, locally and economically tailored approach system required to grow spirulina in the region. The study established the use of food grade organic media with low-cost urea as nitrogen source, a greenhouse average temperature of 30–32 °C in the months between December to March, alkalinity of 5 g/L, mixing frequency of 3 times per day/100 L and partial shading, as the optimum conditions for outdoor cultivation of spirulina. Keywords: Malnutrition, Spirulina, Protein, growth condition